Mesoaxial polydactyly is a major feature in Bardet–Biedl syndrome patients with LZTFL1 (BBS17) mutations. (12th June 2013) - Schaefer, E.; Lauer, J.; Durand, M.; Pelletier, V.; Obringer, C.; Claussmann, A.; Braun, J.‐J.; Redin, C.; Mathis, C.; Muller, J.; Schmidt‐Mutter, C.; Flori, E.; et al.
<x xml:space="preserve">Abstract</x> Ciliopathies are heterogeneous disorders sharing different clinical signs due to a defect at the level of the primary cilia/centrosome complex. Postaxial polydactyly is frequently reported in ciliopathies, especially in Bardet–Biedl syndrome (BBS). Clinical features and genetic results observed in a pair of dizygotic twins with BBS are reported. The following manifestations were present: retinitis pigmentosa, bilateral insertional polydactyly, cognitive impairment and renal dysfunction. X‐rays of the hands confirmed the presence of a 4th mesoaxial extra‐digit with Y‐shaped metacarpal bones. The sequencing of LZTFL1 identified a missense mutation (NM_020347.2: p.Leu87Pro; c.260T>C) and a nonsense mutation (p.Glu260*; c.778G>T), establishing a compound heterozygous status for the twins. A major decrease of LZTFL1 transcript and protein was observed in the patient's fibroblasts. This is the second report of LZTFL1 mutations in BBS patients confirming LZTFL1 as a BBS gene. Interestingly, the only two families reported in literature thus far with LZTFL1 mutations have in common mesoaxial polydactyly, a very uncommon feature for BBS. This special subtype of polydactyly in BBS patients is easily identified on clinical examination and prompts for priority sequencing of LZTFL1 (BBS17).